Beautiful paper cutting : 30 creative projects for cards, gifts, decor, and jewelry (Lark, 2015)
Designers featured: Alli Bartkowski, Amanda Carestio, Candie Cooper, Silvina de Vita, Ellen Deaking, Ali Harrison, Dee Dee Jacq, Rebecca Kedborn, Carlos N. Molina, Cynthia Shaffer, Regina Squier.--About the designers.